2016
DOI: 10.1037/pmu0000139
|View full text |Cite
|
Sign up to set email alerts
|

Listening to classical music results in a positive correlation between spatial reasoning and mindfulness.

Abstract: Music-based interventions have become increasingly popular. However, little is known about the effect of music on spatial reasoning skills and mindfulness. Further, even less is known about how classical music influences the ability of African Americans to enhance spatial reasoning skills and to develop mindfully attentive awareness. Mindfulness is defined as the state of being attentive to and aware of what is taking place in the present moment. Spatial reasoning refers to the ability to mentally manipulate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
9
2
Order By: Relevance
“…Temporary mindfulness meditation training, as a relaxed state of enhanced self-regulation, effectively regulated individuals’ negative moods and non-judging of inner experience, which improved emotion processing [ 35 , 36 , 37 , 38 ]. Mindfulness-based music listening has been shown to regulate negative mood [ 10 , 39 , 40 ], decrease psychological stress and anxiety symptoms [ 40 ], and enhance body awareness [ 30 ] and attentional control [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Temporary mindfulness meditation training, as a relaxed state of enhanced self-regulation, effectively regulated individuals’ negative moods and non-judging of inner experience, which improved emotion processing [ 35 , 36 , 37 , 38 ]. Mindfulness-based music listening has been shown to regulate negative mood [ 10 , 39 , 40 ], decrease psychological stress and anxiety symptoms [ 40 ], and enhance body awareness [ 30 ] and attentional control [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, those who practice mindfulness through meditational exercises on average increase their predisposition to be mindful in daily life, which in effect has shown to contribute towards healthier eating behaviours across time (Dalen et al, 2010;Jordan et al, 2014;Kristeller, Wolever, & Sheets, 2014). In general, there seems to be little research conducted on music and its effect on mindfulness; however, previous studies that have been conducted do suggest a possible association between the two, specifically regarding classical music (Bell et al, 2016). For example, similar to classical music, mindfulness practices are also suggested to have a calming effect amongst participants (e.g., Lauricella, 2014) , and similar neurophysiology amongst those who regularly engage in mindfulness meditation and those who listen to classical music on a daily basis has also been found (Aoun et al, 2005;H€ olzel, Carmody, Vangel, Congleton, Yerramsetti, Gard, & Lazar, 2011;Vuilleumier, 2005).…”
mentioning
confidence: 99%
“…Mindfulness-based music listening can increase listening sensitivity and enjoyment (Anderson, 2016;Baylan et al, 2018), improve well-being (Brown and Ryan, 2003;Rodríguez-Carvajal and Lecuona, 2014;Sorensen et al, 2018;Loo et al, 2020), enhance body awareness and listening experiences (Diaz, 2013;Rodríguez-Carvajal and Lecuona, 2014), and decrease psychological stress and anxiety symptoms (Tomaselli, 2014). Specific musical activities, such as listening to mindfulness music, chorus training, music performance, and music creation, could induce a state of mindfulness meditation, which moderates the absorption of musical stimuli by the participants and affects their emotional experiences (Bell et al, 2016;Lynch and Wilson, 2017;Dvorak and Hernandez-Ruiz, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness meditation, as a state, trait, or clinical intervention, has been widely used in emotion regulation, attention, psychotherapy, and clinical medicine, among other fields (Brown and Ryan, 2003 ; Sahdra et al, 2011 ; Singh et al, 2014 ; Bueno et al, 2015 ; Zanesco et al, 2016 ; Zanesco, 2017 ; Andreu et al, 2019 ; Bailey et al, 2019 ). It has brought many positive effects to people, such as regulated negative emotions, enhanced self-awareness, improved well-being, enhanced psychological function, and reduced stress symptoms, and improved cognitive recovery (Brown and Ryan, 2003 ; Rodríguez-Carvajal and Lecuona, 2014 ; Tomaselli, 2014 ; Anderson, 2016 ; Bell et al, 2016 ; Baylan et al, 2018 ; Sorensen et al, 2018 ; Loo et al, 2020 ; Misba et al, 2020 ). Previous studies have shown a certain relationship between mindfulness meditation and specific music activities (Rodríguez-Carvajal and Lecuona, 2014 ).…”
Section: Introductionmentioning
confidence: 99%